An Investigation of the Use of Lexical Cohesive Devices in Academic Writing Essays of Grade 9 Learners at an American School in Sharjah - Khalil, Abdelhamid (2019)
Writing is considered a challenging skill for L2 learners of English regardless their proficiency level, particularly in terms of achieving coherence and text unity. Research has shown that most L2 learners usually underuse, misuse or overuse cohesive devices that are significantly responsible for maintaining cohesion and coherence in their essay writing. This study aims to investigate the use of lexical cohesive devices for 56 grade 9 L2 learners at an American curriculum school in Sharjah city, UAE. This paper focuses on identifying the frequency of occurrence of six lexical cohesive devices including repetition, synonyms, antonyms, hyponyms, meronyms and collocations in L2 students’ critical review essay writing. It also identifies the correlation between the number of lexical cohesive devices and the writing quality. Furthermore, the study attempts to find the main difficulties encountered by L2 learners regarding the use of lexical cohesive devices in writing. In order to achieve the purpose of the study, the mixed-methods approach was adopted. The quantitative descriptive statistics approach was used to find out the frequency of LCDs in the essay, and the quantitative correlational statistics approach, using Pearson Correlation Coefficient, was implemented to examine the correlation between the number of LCDs and the writing quality. However, the qualitative descriptive approach, using semi-structured interviews of 4 teachers of English and 15 participants, was used to identify the challenges faced by the participants in terms of using LCDs in essay writing. An analysis of the findings demonstrated that repetition and collocations were the most frequently used lexical cohesive ties, while meronyms and hyponyms were the least common in the participants’ writing. There was a moderate positive correlation between cohesive density and the writing quality. The participants faced difficulties dealing with lexical cohesive devices such as lack of proper feedback and correction of cohesive ties in writing, teachers’ inability to balance training L2 learners on all lexical cohesive devices equally and teaching these devices separately instead of delivering them to learners in the context of writing. Overall, it is recommended that teachers teach lexical cohesive devices in the context of reading and writing, and they are advised to clearly indicate their grading criteria in the writing rubric. Furthermore, teachers are recommended to raise learners’ awareness of lexical cohesion and its benefit in terms of achieving text unity and coherence. Further research is needed to investigate the effectiveness of socio-linguistic variables such as participants’ age, sex, writing genres and L2 proficiency level and how they might affect text coherence.